Corynebacterium jeikeium jk0268 Constitutes for the 40 Amino Acid Long PorACj, Which Forms a Homooligomeric and Anion-Selective Cell Wall Channel - Abdali, Narges (Public Library of Science, 2013)
Corynebacterium jeikeium, a resident of human skin, is often associated with multidrug resistant nosocomial infections in immunodepressed patients. C. jeikeium K411 belongs to mycolic acid-containing actinomycetes, the mycolata and contains a channel-forming protein as judged from reconstitution experiments with artificial lipid bilayer experiments. The channel-forming protein was present in detergent treated cell walls and in extracts of whole cells using organic solvents. A gene coding for a 40 amino acid long polypeptide possibly responsible for the pore-forming activity was identified in the known genome of C. jeikeium by its similar chromosomal localization to known porH and porA genes of other Corynebacterium strains. The gene jk0268 was expressed in a porin deficient Corynebacterium glutamicum strain. For purification temporarily histidine-tailed or with a GST-tag at the N-terminus, the homogeneous protein caused channel-forming activity with an average conductance of 1.25 nS in 1M KCl identical to the channels formed by the detergent extracts. Zero-current membrane potential measurements of the voltage dependent channel implied selectivity for anions. This preference is according to single-channel analysis caused by some excess of cationic charges located in the channel lumen formed by oligomeric alpha-helical wheels. The channel has a suggested diameter of 1.4 nm as judged from the permeability of different sized hydrated anions using the Renkin correction factor. Surprisingly, the genome of C. jeikeium contained only one gene coding for a cell wall channel of the PorA/PorH type found in other Corynebacterium species. The possible evolutionary relationship between the heterooligomeric channels formed by certain Corynebacterium strains and the homooligomeric pore of C. jeikeium is discussed.